491 SIROLIMUS AS A RISK FACTOR FOR INCISIONAL HERNIA FOLLOWING LIVER TRANSPLANTATION. (10th December 2015) - Barnes, M. T.; Singh, G.; Jabbour, N.; Genyk, Y.; Sher, L.; Selby, R. R.; Mateo, R.
Abstract : Purpose: In this study, we sought to find the incidence of incisional hernias as a complication of orthotopic liver transplantation (OLT). Patient demographics, clinical history, surgical technique, and treatment with the immunosuppressive (IS) drug sirolimus were among the risk factors evaluated. Methods: We retrospectively reviewed the records of 268 liver transplants that were performed at USC University Hospital between June, 1996 and December, 2003, and included recipients with a six month minimum post-operative survival. Data was collected from hospital records, with lab values recorded at the time of transplant and one month post-transplant. An infection was defined by positive cultures, and sirolimus exposure was noted with any dose of the drug administered during the post-operative hospital stay. Statistical analysis was performed using the equal variance t-test for continuous variables, the Chi-square test or Fisher's exact test (2 tail) for categorical variables. Results: Among the 268 liver transplantations included in this study, 22 were complicated by an incisional hernia, for an incidence rate of 8.2%. The incidence was not significantly affected by differences in patient age, sex, BMI, operating time, incision type, suture material, suture technique, fascia closure technique, wound infection, bacteremia, previous abdominal surgery, presence of diabetes mellitus, or serum bilirubin or albumin levels. There was a significantly greater incidence of incisional hernias in the 128 patients who were exposed to sirolimus, compared with the 130 patients who were not (13.3% with sirolimus vs. 3.8% without; p=0.00731). In addition, patients who developed hernias had significantly higher platelet counts post-transplant (hernia 244 ×103/µl vs. no hernia 183 ×103/µl; p=0.07), although platelet counts in patients given sirolimus showed a significantly greater increase at one month post-transplant (+108 ×103/µl) compared with those who were not given sirolimus (+80 ×103/µl; p=0.025). Conclusions: The use of sirolimus, an effective IS agent used to prevent rejection following OLT, appears to be associated with an increased incidence of incisional hernias. An associated increase in platelet counts may be secondary to differences in IS regimens. Further study is needed to rule out other confounders that may have predisposed recipients treated with sirolimus to hernia formation, and to elucidate a mechanism for sirolimus-induced wound complications.